Patterns of Teachers’ Activity in Biology Classrooms - B. Barquilla, Manuel (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The study attempts to describe practices of biology teachers bv determining the patterns of teachers’ activities in the biology classroom,particularly, the teachers’ pedagogy, time management, motivational skills, and assessing skills. Likewise, it is hoped to determine if the teachers utilize critical and higher order thinking skills. Qualitative and quantitative data were utilized to describe the patterns of teachers’ activities inside the biology classes which occur between the biology teacher and students in the five topics of biology, namely: photosynthesis, cellular respiration, human reproduction and genetics (Mendelian and non Mendelian).The results identified some recognized patterns: subsequent implications and recommendation are formulated.